2008
DOI: 10.1007/s11426-008-0011-x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-assisted pulsed laser evaporation of polyimide thin films and the XPS study

Abstract: Compared with the traditional thin film techniques, the matrix-assisted pulsed laser evaporation (MAPLE) technique has many advantages in the deposition of polymer and organic thin films. It has a wide range of applications in many fields, such as non-linear optics, luminescent devices, electronics, various sensors. We have successfully deposited polyimide thin films by using the MAPLE technique. These films were characterized with XPS. The XPS spectra showed that the single-photon effect is obvious at low las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Complex 3‐dimensional microstructures with different heights and sizes corresponding to the grid were revealed, similar to those found in the literature . Also, analyzing the AFM images from Figure and the roughness parameters written on each image, it was found that the film portions exposed to plasma treatment had the average roughness (Sa) and root mean square roughness (Sq) greater than those covered by the grid, increasing with the value of the plasma power, from 20 to 50 W. This was induced by the oxygen ion bombardment together with the formation of O 2 plasma–generated functional groups . Theoretically in these regions, an improvement in wettability of the surface may occur, attributed both to the increase of the surface roughness and to the formation of polar groups in the surface region .…”
Section: Resultssupporting
confidence: 80%
“…Complex 3‐dimensional microstructures with different heights and sizes corresponding to the grid were revealed, similar to those found in the literature . Also, analyzing the AFM images from Figure and the roughness parameters written on each image, it was found that the film portions exposed to plasma treatment had the average roughness (Sa) and root mean square roughness (Sq) greater than those covered by the grid, increasing with the value of the plasma power, from 20 to 50 W. This was induced by the oxygen ion bombardment together with the formation of O 2 plasma–generated functional groups . Theoretically in these regions, an improvement in wettability of the surface may occur, attributed both to the increase of the surface roughness and to the formation of polar groups in the surface region .…”
Section: Resultssupporting
confidence: 80%
“…Surface roughening of polymer membrane can result from the difference in etching rates of different regions of the polymer during reactive ion etching. 23,31,34 The obtained results indicate that the large increase of arithmetic roughness Ra (Table 3) dramatically reduces the water contact angle values (Fig. 5).…”
Section: Surface Characterization Of Matrimid ® 5218 Lmsmentioning
confidence: 75%
“…Besides, a dramatic change in C 1s core-level spectrum is observed (Fig. 6b), which can be attributed to the formation of uorinated carbon functionalities: 21,22,34,36 CF 2 -CH 2 bond at 285.6 eV, C-F bond at 288.3 eV, CF 2 -CF 2 bond at 290.5 eV and CF 3 -groups at 293.0 eV.…”
Section: Surface Characterization Of Matrimid ® 5218 Lmsmentioning
confidence: 97%
See 1 more Smart Citation
“…These are supported by Pique et al, who showed that organic thin films obtained through MAPLE at laser fluence ranging from 0.01 to 0.5 J∙cm −2 showed changes of the polymer, mostly due to decomposition [ 28 ]. In addition, research by Wang et al, showed that polyimide thin films deposited by MAPLE presented starting material decomposition when the laser fluence decreased to 0.5 J∙cm −2 [ 62 ]. Nevertheless, for all the deposited films, the surface was Zn enriched when compared to the starting control and its imidazole content, like in the experiments conducted by Fangyuan Tian et al, thus demonstrating partial decomposition of ZIF-8 as also shown through XRD and FTIR analysis [ 59 ].…”
Section: Resultsmentioning
confidence: 99%